BISNIS DALAM ISLAM (IMPLEMENTASI PRINSIP-PRINSIP ISLAM DALAM AKTIFITAS EKONOMI BISNIS) - M. Zikwan; Nahei Nahei (Al-Idarah, 2023)
Current business developments provide space for everyone to make creations in business economic activity models. This condition provides opportunities and challenges that become homework for every circle, both business people, academics and even those in authority. The opportunity provided by this condition is the freedom for each individual to develop creativity and business innovation according to the wishes of every society, but this presents a challenge in the form of the growth and development of business economic activities which can violate Islamic principles in transactions and can have a worse impact, namely running a business by making a profit on the suffering of others. Therefore this article seeks to explain the concept of business in Islam with an approach to implementing Islamic principles in business activities. The purpose of this article is to provide an overview of business principles in Islam with a focus on discussing how Islamic principles carry out business economic activities. This article uses a qualitative method with a library research approach. The data were obtained through a literature review of several scientific works both from turat books and from other research results. The conclusion of the results of this article illustrates that Islam gives freedom to every individual to create transaction models and business activities, but the freedom in question does not mean freedom without any barriers in activities. Therefore Islam provides several principles that can be applied in business economic activities which in this article the author summarizes into seven namely, mabadi' ar-rabbaniyyah, an-nubuwah, al-ishlah ijtima'iyyah, al-Jadi, at-tardiyyah, al -ukhuwah, al-hurriyah wal masuliyyah.